An ACVR1R375P pathogenic variant in two families with mild fibrodysplasia ossificans progressiva. Issue 3 (2nd December 2021) - Kaplan, Frederick S.; Groppe, Jay C.; Xu, Meiqi; Towler, O. Will; Grunvald, Eduardo; Kalunian, Kenneth; Kallish, Staci; Al Mukaddam, Mona; Pignolo, Robert J.; Shore, Eileen M.
Abstract: Genetic variants are vital in informing clinical phenotypes, aiding physical diagnosis, guiding genetic counseling, understanding the molecular basis of disease, and potentially stimulating drug development. Here we describe two families with an ultrarare ACVR1 gain‐of‐function pathogenic variant (codon 375, Arginine > Proline; ACVR1 R375P ) responsible for a mild nonclassic fibrodysplasia ossificans progressiva (FOP) phenotype. Both families include people with the ultrarare ACVR1 R375P variant who exhibit features of FOP while other individuals currently do not express any clinical signs of FOP. Thus, the mild ACVR1 R375P variant greatly expands the scope and understanding of this rare disorder.